Afterword: Some ontological thoughts on friendship - Jarrett Zigon (Suomen Antropologi, 2014)
In raising the question of the relation between the two experiential modalities of friendship and morality, this collection of essays has opened a clearing for novel ways of doing and thinking friendship anthropologically. The path revealed by means of this clearing parallels that of the order of the essays in this collection.